Design and synthesis of novel poly (aryl ether ketones) containing trifluoromethyl and trifluoromethoxy groups. Issue 1 (31st December 2023) - Liu, Xiaolong; Sun, Yunlong; Chen, Yue; Zhao, Zhongfu; Wang, Zhipeng; Zhou, Guangyuan
ABSTRACT: The high-frequency and high-speed communication in the 5 G era puts forward requirements for the dielectric properties of polymers. Introducing fluorine into poly(ary ether ketone) can improve its dielectric properties. In this work, by introducing the fluorine group strategy, we successfully designed and synthesized three novel trifluoromethyl (−CF3 ) or trifluoromethoxy (−OCF3 )-containing bisphenol monomers and their F-substitution PEK-based polymers (PEK-Ins). All these PEK-Ins exhibited good thermal, mechanical and dielectric properties. The T d5% of the three polymers is all higher than 520℃. The free volume fraction of novel polymers increased from 3.75% to 5.72%. Among the three polymers, exhibited the lowest dielectric constant of the films is 2.839, and the dielectric loss is 0.0048, ascribing to the increasing free volume. The Young's modulus of the polymer film is as high as 2.9 GPa and the tensile strength is as high as 84 MPa. PEK-Ins reduced the dielectric constant by introducing a low fluorine content. This study provides a new way to design PEK to synthesize low dielectric constant polymers.